Evaluation of Transport Parameters in MoS2/Graphene Junction Devices Fabricated by Chemical Vapor Deposition - Kim, Young Chul; Nguyen, Van Tu; Lee, Soonil; Park, Ji Yong; Ahn, Yeong Hwan (ACS Applied Materials and Interfaces, 2018)
We demonstrated imaging of the depletion layer in a MoS2/graphene heterojunction fabricated by chemical vapor deposition and obtained their transport parameters such as diffusion length, lifetime, and mobility by using scanning photocurrent microscopy (SPCM). The device exhibited a n-type operation, which was determined by the MoS2 layer with a lower mobility. The SPCM revealed the presence of the depletion layer at the heterojunction, whereas graphene provided an excellent electrical contact for the MoS2 layer without resulting in a rectifying behavior, even if they were anchored within a very short range. The polarity of the photocurrent signal switched when we applied a drain-source bias voltage, from which we extracted the potential barrier at the junction. More importantly, a bias-dependent SPCM allowed us to simultaneously record the diffusion lengths of both majority and minority carriers for the respective MoS2 and graphene layers. By combining the diffusion lengths with the lifetimes measured by femtosecond SPCM, we determined the electron and hole mobilities in each layer, from which we found that the electron mobility (160 cm2 V-1 s-1) was higher than the hole mobility (80 cm2 V-1 s-1) in MoS2, whereas the hole mobility (15 000 cm2 V-1 s-1) was relatively higher in graphene.
Keywords: Diffusion length; Femtosecond pump probe spectroscopy; junction; MoS2; Scanning photocurrent microscopies; diffusion length; femtosecond pump-probe spectroscopy; graphene; junction; mobility; MoS2; scanning photocurrent microscopy